PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENGGUNAKAN KIT HIDROSTATIKA DAN PANAS KONSEP TEKANAN - HERNETA FATIRANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This research was carried out with the aim of analyzing the skills of class VIII students at SMP Negeri 1 Hulu Sungai Tengah in using the Hydrostatics and Heat KIT on the concept of pressure using the discovery learning model. This type of research includes quantitative descriptive where data about student skills is analyzed descriptively based on the percent value (percentage) achieved. The instrument used in this research was an observation sheet about student skills. The results of the research show that there is an increase in the percentage of skills obtained by students at each meeting and in each cycle from 46.50% in cycle I, meeting 1 in the